Extensive Literature Review On Green Logistics 5.0 With Ai Integration - P. Sivasankaran (Journal of Advanced Research in Service Management, 2025)
Green Logistics 5.0 combines cutting-edge technologies like blockchain and artificial intelligence with a human-centred approach to create a logistics industry that is sustainable, strong, and efficient. This evolution concentrates on supply chain optimisation for environmental benefits through methods including route optimisation, packaging waste reduction, and warehouse efficiency enhancement, while allowing human workers to collaborate with these intelligent technologies. A review of logistics 5.0 and its effects on international supply chain systems has been attempted in this research. To examine the effects of logistics 5.0 on highly sustainable systems, data was collected from a variety of publications. Green Logistics 5.0 emphasises a human-AI synergy where technology supports and enhances human decision-making, as opposed to the automation-focused Logistics 4.0. Instead of having AI-powered systems replace workers, this entails retraining them to collaborate with them.